Quarter Life Crisis Dalam Pandangan Hadis - Armayani, Ela (SHAHIH (Jurnal Ilmu Kewahyuan), 2024)
In the Islamic context, understanding the quarter life crisis can be linked to the values taught in the hadith, which offer guidance for facing life's challenges with patience, confidence and spiritual introspection. This research aims to analyze the quarter life crisis phenomenon from a hadith perspective, by exploring moral and spiritual guidance that is relevant for the younger generation. This study is expected to provide in-depth insight into how Islamic values can help individuals overcome life crises and achieve inner peace. The formulation of this research problem includes: What is the quarter life crisis and what is the quarter life crisis from a hadith perspective? This research uses a qualitative method with a descriptive-analytic approach. Primary data is taken from the relevant hadith books which are included in the al-Tis'ah pole, and the sharah book. The analysis was carried out by reviewing hadiths related to youth, life confusion, motivation, and time management. The research results show that the Prophet paid great attention to the development phase of youth. Hadiths related to the importance of time, endeavor, trust, and maintaining a relationship with Allah SWT. providing practical and spiritual solutions to overcome the crisis. Values such as self introspection (muhasabah), optimism, and seeking wisdom in every test of life are the keys to overcoming the quarter life crisis. The conclusion of this research is that the hadith provides a comprehensive foundation for facing the quarter life crisis. Implementing hadith values in daily life can help individuals pass through this phase more wisely and deeply, thereby building a more meaningful and balanced life. It is hoped that this research can beco